DIMENSI KEMASLAHATAN DALAM LARANGAN JUAL BELI GHARAR - ., Suprihatin (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2010)
This article explain about maslahah in the forbidden of gharar (risk). Gharar means doubtfulness or uncertainty as in the case of not knowing whether something will take place or not; this excludes the unknown. Gharar also means ignorance and this can be when the subject matter of sale is unknown. Gharar is the risk where the probability of existence and the probability non-existence have the same value?. There is a consensus among interpreters of the Qur?an that Gharar is vanity (al-bathil). Gharar is unlawful because it is prohibited by Sharia. So, Gharar like maysir (gambling) is not permitted or forbidden by Sharia. The forbidden of Gharar besides is based on Sharia, also is based on maslahah. Some jurists Moslems said that Gharar is not permitted by Islamic jurisprudence (fiqh) because to avoid dispute and gambling. The forbidden of Gharar also is based on belief (iman) to God (Allah) as a Law Giver (al-Hakim) and goodness in the transaction of salling.